2014
DOI: 10.1245/s10434-014-4071-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ultrasound-Guided Lymph Node Biopsy in Axillary Staging of Invasive Breast Cancer in the Post-ACOSOG Z0011 Trial Era

Abstract: These results suggest that ultrasound-positive patients have less favorable disease characteristics and a worse prognosis than SN-positive patients. Therefore, we conclude that omitting an ALND is as yet only applicable, as concluded in the Z0011, in patients with a positive SLNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 27 publications
8
70
1
2
Order By: Relevance
“…Katz To our opinion the primary axillary staging process should be a relevant factor in this decision model. 25 Finally, we agree with Cserni et al that it is imperative that such tools should be institutionally validated to reveal which predictive tool works best in which individual institute. 18,19 Such a development than would be the next step in the ongoing paradigm shift in axillary breast cancer treatment: from the treatment of "all -except", towards the treatment of "none -unless".…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 81%
See 2 more Smart Citations
“…Katz To our opinion the primary axillary staging process should be a relevant factor in this decision model. 25 Finally, we agree with Cserni et al that it is imperative that such tools should be institutionally validated to reveal which predictive tool works best in which individual institute. 18,19 Such a development than would be the next step in the ongoing paradigm shift in axillary breast cancer treatment: from the treatment of "all -except", towards the treatment of "none -unless".…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 81%
“…24 24 Recently, it has been shown that due to significant differences in patient characteristics between those selected by ultrasound guided lymph node biopsy(UGLNB) versus immediate SLNB, the ACOSOG Z0011 trial conclusions seem as yet only applicable to patients with a positive axilla found by SLNB. 25 This is important, since the selection process differs quite essentially between patients in the USA and Europe, because axillary work up in Europe includes standard ultrasound of the axilla. The latter work up is associated with more extensive nodal disease and worse prognosis and thus not comparable to patients from the original USA Z0011 trial data.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of LVI has been found to be significantly related to positivity of the secondary lymph node involvement, as well as the primary tumour size and the size of the sentinel lymph node metastasis [5,[13][14][15]. When the risk for secondary lymph node involvement is considered high in patients with positive sentinel lymph node involvement, aggressive axillary lymphadenectomy might be recommended at surgery [16][17][18]. However, preoperative evaluation of LVI is difficult via percutaneous biopsy because histological examination of the biopsy specimen without peritumoral tissue does not provide information on the LVI just outside the tumour.…”
Section: Introductionmentioning
confidence: 99%
“…The authors and ensuing discussants suggested redefinition of the role of AUS to select patients with a high axillary disease burden who are likely to benefit from multimodality therapy including ALND. 10 Reports of smaller series also corroborate the value of AUS and FNA for identification of patients likely to have a high axillary disease burden at operation. 11,12 Many forward-thinking surgical oncologists are now evaluating how to stratify patients into three groups: (1) those for whom axillary surgery might be avoided altogether, (2) those for whom SLNR alone might be important to for nodal staging and suffice for those with (limited) node-positive disease, and (3) those who will derive the greatest potential benefit from ALND directly or after a positive SLNR within the context of multimodality therapy.…”
mentioning
confidence: 71%